2014
DOI: 10.7740/kjcs.2014.59.3.332
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response and Nutrient Content of Cowpea Sprouts Based on Growth Temperature and Genetic Resources

Abstract: The purpose of this study was to establish the optimal growth temperature and to select genetic resources for production of cowpea sprouts. Seowon was treated between 15℃ and 30℃ at intervals of 3℃ to investigate growth temperature. Twelve resources, including Seowon, IT154149, IT154153, Tvu7426, and Tvu7778, were used for cultivating sprouts at a temperature of 27℃. The yield ratio of cowpea sprouts was highest at 27℃ (657%), and was reduced when growth temperature was decreased. The hard seed rate was lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Results revealed that cowpea leaves are a rich source of minerals such as iron, potassium, calcium, magnesium, phosphorus, manganese and zinc ( Table 2 ). The mineral contents in cowpeas in this study was in the same range with some of the green leafy vegetables, including C. gynandra ( Schönfeldt and Pretorius, 2011 ; Okonya and Maass, 2014 ; Kim et al., 2014 ; Omondi et al., 2017 ). However fluctuations can occur due to changes in production conditions, temperature and light just as seen in the carbohydrates dynamics.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Results revealed that cowpea leaves are a rich source of minerals such as iron, potassium, calcium, magnesium, phosphorus, manganese and zinc ( Table 2 ). The mineral contents in cowpeas in this study was in the same range with some of the green leafy vegetables, including C. gynandra ( Schönfeldt and Pretorius, 2011 ; Okonya and Maass, 2014 ; Kim et al., 2014 ; Omondi et al., 2017 ). However fluctuations can occur due to changes in production conditions, temperature and light just as seen in the carbohydrates dynamics.…”
Section: Discussionsupporting
confidence: 57%
“…However, calcium decreased with age while Fe and Mn increased ( Table 2 ). Previous studies have reported a wide variability of minerals in different cowpeas cultivars ( Kim et al., 2014 ). However, little information is available about dynamics of mineral elements during the development of leafy vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritionally, cowpea seeds protein shows a prevalence of glutamine/glutamic acid (16.5–18.8 g 16 g −1 N), asparagine/aspartic acid (11.4–13.2 g 16 g −1 N), and phenylalanine + tyrosine (7.5–10.2 g 16 g −1 N), as well as a secondary prevalence of arginine, leucine, lysine, valine and proline . The same ranking is observed in leaves, even though cowpea leaf protein, based on their amino acid content, is more than two‐fold higher (Table ) to that described for seeds (24.3–45.3, 17.0–26.7, and 19.1–23.7 g 16 g −1 N, for glutamine/glutamic acid, asparagine/aspartic acid, and phenylalanine + tyrosine, respectively) …”
Section: Nutritional Composition Of Cowpeamentioning
confidence: 75%
“…Thus, potassium is the most abundant mineral in seeds and leaves, with contents ranging from 1.9 to 28.9 g kg −1 . Of particular importance are the high contents of calcium (383–10 620 and 398.0–8050.0 × 10 −3 g kg −1 in seeds and leaves, respectively), zinc (8.1–118.0 and 3.4–129.1 × 10 −3 g kg −1 in seeds and leaves, respectively), and iron (6.9–218.0 and 16.2–772.9 × 10 −3 g kg −1 in seeds and leaves, respectively) . This mineral composition emphasises the value of cowpea fulfilling the recommended daily intake in a similar way as other legumes .…”
Section: Nutritional Composition Of Cowpeamentioning
confidence: 86%
See 1 more Smart Citation